Mechanisms of Laser-Tissue Interaction: II. Tissue Thermal Properties - Ansari, Mohammad Ali; Erfanzadeh, Mohsen; Mohajerani, Ezeddin (Journal of Lasers in Medical Sciences, 2013)
Laser-tissue interaction is of great interest due to its significant application in biomedical optics in both diagnostic and treatment purposes. Major aspects of the laser-tissue interaction which has to be considered in biomedical studies are the thermal properties of the tissue and the thermal changes caused by the interaction of light and tissue. In this review paper the effects of light on the tissue at different temperatures are discussed. Then, due to the noticeable importance of studying the heat transfer quantitatively, the equations governing this phenomenon are presented. Finally a method of medical diagnosis called thermography and some of its applications are explained.